PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN CARRD.CO TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS V SD - Rania Zahra; Fadhilah Khairani; Nindy Profithasari; Frida Destini (STKIP Subang, 2025)
The problem in this study was the low creative thinking ability of fifth-gradeelementary school students. This study aimed to determine the effect of theProject-Based Learning (PjBL) model assisted by the carrd.co media on students’creative thinking abilities in the IPAS subject for Grade V at SD Aisyiyah MetroSelatan. This study used a quantitative research method with an experimental typein the form of a quasi-experimental design with a nonequivalent control groupdesign. The population in this study consisted of 61 students. The samplingtechnique used was saturated sampling. Data collection was carried out using atest technique in the form of essay questions. The data analysis technique usedsimple regression analysis. Data were collected through pretest and posttestbased on indicators of creative thinking, namely fluency, flexibility, originality, andelaboration. The results of the simple regression test showed that Fcount & Ftable,thus Ha was accepted. The results of this study indicated that the Project-BasedLearning model assisted by carrd.co media had a positive and significant effect onthe creative thinking ability of students in IPAS learning in grade V at SD AisyiyahMetro Selatan.